The Role of Employee Engagement & Digital Leadership in Enhancing Service Quality of Public Service in Rural Goverment - Wakhyuni, Emi; Setiawan, Abdi (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the influence of Employee Engagement and Digital Leadership on the quality of public services in rural local governments. The research is grounded in the persistent challenges faced by rural public service institutions, including limited resources, suboptimal utilization of digital technology, and low levels of employee involvement in service delivery. A quantitative approach was employed using a survey method with 150 respondents consisting of local government employees in rural areas. Data were analyzed using multiple linear regression, supported by classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. The findings indicate that Employee Engagement has a positive and significant effect on public service quality. Employees with higher engagement levels tend to demonstrate stronger motivation, commitment, and responsiveness in delivering public services. Digital Leadership also shows a significant positive influence on service quality, particularly through leaders’ ability to utilize digital technologies, provide data-driven direction, and encourage collaborative work through digital platforms. Simultaneously, both variables significantly contribute to improving the quality of public services. The classical assumption tests confirm that the regression model used in this study meets the required statistical assumptions. These results highlight that improving public service quality in rural local governments requires strengthening employee engagement and enhancing digital leadership capacity. The study provides valuable insights for local governments in designing human resource development strategies and supporting digital transformation in rural public service delivery.